2020
DOI: 10.1186/s12881-020-01036-8
|View full text |Cite
|
Sign up to set email alerts
|

Osteoprotegerin gene polymorphisms and otosclerosis: an additional genetic association study, multilocus interaction and meta-analysis

Abstract: Background: Otosclerosis (OTSC) is among the most common causes of a late-onset hearing loss in adults and is characterized by an abnormal bone growth in the otic capsule. Alteration in the osteoprotegerin (OPG) expression has been suggested in the implication of OTSC pathogenesis. Methods: A case-control association study of rs2228568, rs7844539, rs3102734 and rs2073618 single nucleotide polymorphisms (SNPs) in the OPG gene was performed in a Tunisian-North African population composed of 183 unrelated OTSC pa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…Given the critical role of the RANK/RANKL/OPG signaling pathway in maintaining/ regulating proper bone metabolism, SNPs in these pathway genes could also be determinants for bone alterations and the onset of pathological conditions. We provided evidence previously that rs3102734 and rs2073618 variants of the OPG gene are associated with OTSC in a Tunisian North-African ethnic population ( 15 ). To the best of our knowledge, based on a deep literature review and the Mastermind database search, a widely-used bioinformatics platform of a comprehensive genomic association, this is the first study elucidating the roles of genetic association and DNA methylation modifications of TNFSF11 gene in OTSC ( Figure 5 ).…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Given the critical role of the RANK/RANKL/OPG signaling pathway in maintaining/ regulating proper bone metabolism, SNPs in these pathway genes could also be determinants for bone alterations and the onset of pathological conditions. We provided evidence previously that rs3102734 and rs2073618 variants of the OPG gene are associated with OTSC in a Tunisian North-African ethnic population ( 15 ). To the best of our knowledge, based on a deep literature review and the Mastermind database search, a widely-used bioinformatics platform of a comprehensive genomic association, this is the first study elucidating the roles of genetic association and DNA methylation modifications of TNFSF11 gene in OTSC ( Figure 5 ).…”
Section: Discussionmentioning
confidence: 84%
“…Nevertheless, case-control, linkage, and association studies have evoked an eventual association of several genes with OTSC in different ethnic populations. These studies reported the possible implications of different genes, including COL1A1, COL1A2 ( 9 ), FGF2 ( 10 ), TGF β 1, BMP2 ( 11 , 12 ), BMP4 ( 11 , 13 ), AGT, ACE ( 14 ), and OPG ( 15 , 16 ). In addition, a genome-wide association study (GWAS) conducted in Belgian-Dutch individuals revealed that a region on chromosome 7q22.1 within the RELN gene is strongly associated with OTSC ( 17 ).…”
Section: Introductionmentioning
confidence: 99%
“…OPG has an important anti-osteoclastogenic action and acts indirectly by opposing the anti-TNF-alpha and RAK/RANKL actions. 36 Preliminary studies, not used for clinical practice but in animals, are promising due to the potential action of OPG in the early stage of otosclerotic disease. Therefore, its use should be encouraged in research, initially, only after safety and efficacy have been evaluated in preliminary human studies.…”
Section: Discussion ‒ Treatmentmentioning
confidence: 99%
“…Compared with normal stapes tissue samples, the mRNA expression of OPG is reduced in patients with otosclerosis. 35 , 36 In addition, homozygous mutations in TNFRSF11B play a role in Paget’s disease, which may also lead to hearing loss, 37 making it an interesting candidate gene for otosclerosis.…”
Section: Introductionmentioning
confidence: 99%
“…Despite intensive study on OTSC, till date ten monogenic loci has been mapped but have not yet identified the causal genes [ 4 , 5 ]. Several case-control studies reported a significant association of SNPs in COL1A1 [ 6 , 7 ] , TGF-β1 [ 8 , 9 ] , BMP2 [ 10 ], BMP4 [ 7 , 10 ] and OPG [ 11 , 12 ] genes with OTSC in different populations. Recently, high throughput sequencing has spotted certain pathogenic variants in MEPE , ACAN and SERPINF1 genes with unsettled pathogenicity [ 5 , 13 ].…”
Section: Introductionmentioning
confidence: 99%